Model Laboratorium Pola Aliran Pada Krib Permeable Terhadap Variasi Jarak Antar Krib Dan Debit Alirandi Sungai Berbelok - Zikri, Ahmad; Mudjiatko, Mudjiatko; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Crib is a structure that used to adjust the direction of flow of the river to protect riverbanks from direct flow. Laboratory model used to demonstrate the phenomenon of flow patterns that occur in the river’s turn around the crib. Crib models that will be used in this study is a crib with a permeable type with dimensions 0.15 m length, 0.03 m width and 0.15 m height. Materials to be used in permeable crib is a plain iron with 10 mm diameter. The variable in this study is flow rate and distance between the crib. The flow rate varies 0.00134 m³/sec, 0.00298 m³/sec and 0.0056 m³/sec. The distance between crib varies between 30 cm, 40 cm and 50 cm from the beginning of the turn of the river entrance. The flow velocity that occurs around the crib shrink in every variety test. The flow patterns on every variation of the distance between crib with 0.00134 m³/sec of flow rate, the vortex of flow occurs in the early part of the crib. The flow patterns on every variation of the distance between crib with 0.00298 m³/sec of flow rate, the vortex of flow occurs in the early part of the crib. The flow patterns on every variation of the distance between crib with 0.0056 m³/sec of flow rate, the vortex of flow occurs on the side of the crib end. The length of the vortex occurs differently in each variation of the distance between crib at 30 cm, the length of the vortex is relatively short. At a distance of 40 cm, the length of the vortex is relatively long and at a distance of 50 cm, the length of the vortex is quite long.Key word : flow pattern, river’s turn, permeable crib